Executive Function Performance in Young Adults When Cycling at an Active Workstation: An fNIRS Study - Huang, Tao (Int J Environ Res Public Health, 2019)
Background: This study aimed to investigate the effects of self-paced cycling at an active workstation on executive functions and cortical activity. Methods: In a crossover study design, 37 young adults (45.9% females) were randomly assigned to the following two task conditions: (1) performing cognitive tests during sitting, (2) performing cognitive tests while cycling at an active workstation. Executive functions were assessed by the Stroop color and word test and the task-switching paradigm. Cortical activity was monitored using a multi-channel functional near-infrared spectroscopy (fNIRS) system. Results: The behavioral results showed that there were no significant differences on the Stroop interference effects (P = 0.66) between the sitting and the cycling conditions. In all probability, no differences on the global switch costs (P = 0.90) and local switch costs (P = 0.67) were observed between the sitting and the cycling conditions. For the fNIRS results, the oxygenated hemoglobin (oxy-Hb) in response to the Stroop interference in channels 5, 10, and 12 were decreased during the cycling condition (all Ps < 0.05, FDR-corrected). Conversely, the oxy-Hb associated with the global switch costs in channels 3, 29, and 31 were increased during the cycling condition (all Ps < 0.05, FDR-corrected). Conclusions: The findings indicated that behavioral performances on executive functions were not affected by cycling at an active workstation, while cognitive resources were reallocated during cycling at an active workstation.